Inhibition of Human γδ T Cell Proliferation and Effector Functions by Neutrophil Serine Proteases. (December 2014) - Fazio, J.; Kalyan, S.; Wesch, D.; Kabelitz, D.
Abstract Human peripheral blood γδ T cells expressing the Vγ9Vδ2 T cell receptor are activated by microbial or endogenous pyrophosphate antigens and indirectly by nitrogen‐containing bisphosphonates. Apart from proliferation, such phosphoantigens induce proinflammatory cytokine production including TNF‐α and IFN‐γ and trigger cytotoxic effector function. Neutrophil granulocytes are known to modulate T cell activation. The neutrophil serine proteases proteinase 3, elastase and cathepsin G have multiple potential targets and promote microbial killing. In this study, we investigated the effect of the three serine proteases on the in vitro proliferation and effector functions of γδ T cells cultured in serum‐free medium. All three proteases inhibited the proliferative activity, suppressed the cytokine production and decreased the cytotoxicity of γδ T cells. Further studies indicated that proteolytic cleavage of IL‐2 and modulation of butyrophilin 3A1 (CD277) expression might contribute to the overall inhibition.